Independent Evaluation Office : Evaluation of the Financial Sector Assessment Program (FSAP). (Policy Papers; Policy Paper ;, 2006)
This evaluation assesses the effectiveness of the Financial Sector Assessment Program (FSAP) from the perspective of the IMF. A parallel evaluation by the World Bank's OED assesses the World Bank's role. The FSAP was established in 1999 to provide advice to strengthen the financial systems of member countries by facilitating early detection of financial sector vulnerabilities and helping to identify financial sector development needs.